PRODUCTION OF SOYBEAN TEMPEH WITH RHIZOPUS OLIGOSPORUS TISTR 3089 STARTER POWDER IN HOUSEHOLD LEVEL AND USE TO SUBSTITUTE MEAT IN SEASONING POWDER - Chunlakan, Phondaran; Chueamchaitrakun, Piyaporn (Life Sciences and Environment Journal, 2017)
This study aims to expand the production of soybean tempeh from laboratory scale to the household level and, to use soybean tempeh substitutes in seasoning powder. The results showed that the optimum process of soybean tempeh in the household level involved, soybean 2.00 kg, soaking for 16 hr, peeling membrane, cooking in water (100oC) for 40 min, draining water, adding 5.00% (w/w) starter powder of R. oligosporus TISTR 3089, mixing, putting mixed soybean on aluminum tray, pelletizing, covering with perforated plastic bag and incubating at room temperature (28±3oC) for 18 hr, steaming at 100oC for 10 min, drying fermented soybean at 60oC for 10 hr. Soybean tempeh had a good appearance and had the qualities not significant compared laboratory soybean tempeh production. Sensory evaluation using consumer preference test and just about right (JAR) by untrained panels (N=30) showed that consumer liking scores of all attributes of seasoning powder used soybean tempeh 8.00 and 10.00% were not significantly different (p>0.05). The seasoning powder used soybean tempeh (soup) 10% gave all attributes perceived by over 70% of consumers as JAR intensities. The optimum formula of seasoning powder from soybean tempeh consisted of 10.00% soybean tempeh powder, 40.00% salt, 16.00% sugar, 30.00% monosodium glutamate and 4.00% garlic powder respectively. Regard to consumer testing (N=30), consumers liked seasoning powder from soybean tempeh in the level of moderate to high with the overall liking score of 7.63.